Synthesis of Different Sizes TiO2 and Photovoltaic Performance in Dye-Sensitized Solar Cells - Mahmoud, Sawsan A.; Mohamed, Basma S.; Killa, H. M. (Frontiers in Materials, 2021)
For more than 2 decades, extensive research has been done in the field of Dye-Sensitized Solar Cells (DSSCs) due to their low cost, easy preparation methodology, less toxicity, and ease of production. In this work, the performance of DSSCs containing different particle sizes is studied. N2-doped TiO2 was prepared by the sol-gel method, controlling the particle size through the addition of different H2O/Ti mole ratios R = 0, 20, 30, and 40. The dried samples at 100°C were characterized by X-ray diffraction, Optical Properties, High-Resolution Transmission Electron Microscope, Scanning Electron Microscope, Fourier-Transform Infrared Spectroscopy, N2-Adsorption-Desorption Isotherm, Raman Spectroscopy, and Dynamic Light Scattering (DLS). DLS results show that the size of TiO2 decreases as the H2O/TiO2 content increases from 0 to 40. It is found that TiO2 nanoparticles with smaller particle size distribution has the lowest conversion efficiency of 0.95% with H2O/Ti ratio = 40, and the photoelectrode with higher size has a conversion efficiency of 1.59% for the water-free sample. This could be explained as the larger particles have better dye adsorption, indicating that it has an effective surface area for greater photon absorption and electron-hole generation. The results also indicate that trimodal distribution with larger size also absorbs different wavelengths due to the broad distribution of the particle size.